2016
DOI: 10.1038/ncomms10740
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis of three Pneumocystis species reveals adaptation mechanisms to life exclusively in mammalian hosts

Abstract: Pneumocystis jirovecii is a major cause of life-threatening pneumonia in immunosuppressed patients including transplant recipients and those with HIV/AIDS, yet surprisingly little is known about the biology of this fungal pathogen. Here we report near complete genome assemblies for three Pneumocystis species that infect humans, rats and mice. Pneumocystis genomes are highly compact relative to other fungi, with substantial reductions of ribosomal RNA genes, transporters, transcription factors and many metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
381
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(402 citation statements)
references
References 74 publications
18
381
1
2
Order By: Relevance
“…More recently, an intriguing study by Rapaka and colleagues (15) suggested that mice infected with P. murina (Pm) could generate increased levels of IgM antibodies against fungal carbohydrates, including GlcNAc-containing carbohydrates. Recently, however, it has been shown that, although Pneumocystis species contain chitin chaperone proteins implicated in proper transportation of major chitin synthases to the cell membrane in yeast, the genomes of Pneumocystis species lack major chitin synthase or chitin-degrading chitinase enzymes (5). In this light, we initiated a comprehensive analysis of the various enzymes potentially leading to the synthesis of GlcNAc in Pneumocystis organisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, an intriguing study by Rapaka and colleagues (15) suggested that mice infected with P. murina (Pm) could generate increased levels of IgM antibodies against fungal carbohydrates, including GlcNAc-containing carbohydrates. Recently, however, it has been shown that, although Pneumocystis species contain chitin chaperone proteins implicated in proper transportation of major chitin synthases to the cell membrane in yeast, the genomes of Pneumocystis species lack major chitin synthase or chitin-degrading chitinase enzymes (5). In this light, we initiated a comprehensive analysis of the various enzymes potentially leading to the synthesis of GlcNAc in Pneumocystis organisms.…”
mentioning
confidence: 99%
“…The cell surface of the pathogenic fungal species represented by Pneumocystis organisms have not been fully elucidated, but are known to contain b-1,3 and b-1,6 glucans, and the major surface mannoserich glycoproteins, variously termed major surface glycoprotein (MSG) or glycoprotein A (gpA) (3)(4)(5). We and others have shown that the Pneumocystis species contain b-glucan synthetases that can be inhibited by specific b-glucan inhibitors, such as the echinocandins, pneumocandins, and newly generated compounds (3,4,6,7).…”
mentioning
confidence: 99%
“…Both stages express surface glycoproteins and mannoproteins, which may serve as pathogen-associated molecular patterns (PAMPs) that could interact with receptors on phagocytic cells (17)(18)(19). Neither life form expresses chitin or ␣-glucans (20).…”
mentioning
confidence: 99%
“…A total of 14 and 16 MG192 variants, with 1 to 8 variants per time point, were identified from each of the two animals. It is likely that the MG192 variants detected may not represent all variants in each isolate studied and that additional variants could be detected if a larger number of plasmid clones were stud- ied or using the newly developed high-throughput long-read PacBio SMRT sequencing technology (19), though currently this technology is not widely available or affordable (20,24). Using average numbers of nucleotide and predicted amino acid changes at each time point, we observed a significant increase of sequence changes over time during an 11-to 13-week period of infection in both animals ( Table 1).…”
Section: Discussionmentioning
confidence: 99%